PENGGUNAAN SISTEM SANKSI PIDANA PADA PELAKU TINDAK PIDANA KORPORASI - Ahmad, Ahmad (Ensiklopedia Sosial Review, 2022)
The acceptance of the corporation as a subject of criminal law who is considered to be able to commit a criminal act and can be criminally responsible for it will of course lead to other consequences in its application. Various consequences or problems that can arise are reflected in the question of getting a death penalty or imprisonment as regulated in article 10 of the Criminal Code which is applied to a corporation. Or can the “corporate death penalty” and “corporate imprisonment” as stated by Brickey be regarded as a death penalty or imprisonment for a corporation? When compared with the provisions in Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, precisely in article 2 paragraph (2) and article 18 paragraph (1) point c and point d According to this law, in the author's opinion, basically the "corporate death penalty" as stated by Brickey is the same as the provisions of "all or part of the company closure" and "corporate imprisonment" which is basically the same as the provision of "all or part revocation of certain rights or elimination of all or part of certain profits” as regulated in Article 18 paragraph (1) point c and point d of this Law. In addition, if you look at the provisions in Article 2 paragraph (2) which states that: "In the case of a criminal act of corruption as referred to in paragraph (1) carried out under certain circumstances, the death penalty can be imposed". And when viewed from the explanation it is stipulated that: "what is meant by "certain circumstances" is if the crime is committed against funds for overcoming dangerous conditions, national natural disasters, overcoming the consequences of widespread social unrest, overcoming economic crises, and occurring repetition of corruption.Keywords: System, Criminal Sanctions, Criminal Actors, Corporations.